Trends in milkfish fry production in Sofronio Española, Palawan, Philippines with notes on 12-year province-wide production - Villalva, Salvador D.; Dolorosa, Roger G. (2014)
The gathering of wild milkfish fry in the Philippines remains an important livelihood activity among the coastal inhabitants as the milkfish growers continue to prefer the fry harvested from the wild over those produced from hatchery. However, up to date statistics on fry production from the wild is lacking. Given such shortage of information, the volume of fry and catch per unit effort (CPUE) from the two coastal villages in the municipality of Sofronio Española, Palawan were determined; and the 12-year data on volume of fry harvested within the province of Palawan were obtained from two major fry buyers in Puerto Princesa City. In Sofronio Española, the catch in 2011 was about 50% lower than in 2009; while the CPUEs in 2011 largely varied between the two villages. The dwindling volume of fry between 2000 and 2012 calls for further study to determine the causes of this decline which could be used as basis in proposing a management plan to sustain both fry and milkfish industry.
Keywords: Milkfish industry -- Palawan; Fish production